Establishment of a condition-specific quality-of-life questionnaire for children born with esophageal atresia aged 2–7 across 14 countries - Dellenmark-Blom, Michaela (Frontiers in Pediatrics, 2023)
Background: Esophageal atresia (EA) is a rare congenital anomaly characterized by a discontinuity of the esophagus. Following surgical repair, survival rates have improved dramatically the past decenniums and today exceed 90%, but the children commonly present with esophageal and respiratory morbidity. In 2018, a condition-specific quality-of-life questionnaire for children with esophageal atresia (EA) aged 2-7 in Sweden-Germany was finalized (The EA-QOL questionnaire). The study aim was to describe the evaluation of the new translations across 12 new countries in Europe, Asia, Africa, Central-and North America.Methods: Following forward-backward translation into the new languages, the 17-item EA-QOL questionnaire was tested in cognitive debriefing interviews with parents of children with EA aged 2-7. Parents rated if each item was easy to understand (clarity) and sensitive to answer (interference with personal integrity). They could skip responding to a non-applicable/problematic item and give open comments. Predefined psychometric criteria were used; item clarity ≥80%/item sensitive to answer ≤20%/item feasibility <5% missing item responses. The decision to modify the translation was based on native expert, patient stakeholder, and instrument developer review, and the need for harmonization between translations.Results: Similar to findings in the Swedish-German cognitive debriefing, the cross-cultural analysis of input from 116 parents from 12 new countries (4-14 parents, median 9 parents/country) showed that all items in the EA-QOL questionnaire fulfilled the criteria for item clarity ≥80% and sensitive to answer (ranging from 1-4.5%), although results varied between countries. Four items had missing responses between 5.2%-13.4%, three within the same domain and were in line with parents' explanations. Poor translations and feasibility were improved.Based on parent input, the collaboration between native experts, patient stakeholders, and instrument developers, a linguistic version of the EA-QOL questionnaire for children aged 2-7 for use in and across 14 countries has been established. This will open the doors for a new chapter in outcome research, registries, and clinical practice concerning children with EA. In the long-term, this will help increase knowledge of the disease's burden, promote patient-centeredness, exchange of information between nations, and strengthen evidence-based treatments for children born with EA.